1966
DOI: 10.1042/bj0980342
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid composition of the maturing rat testis

Abstract: 1. The lipids and fatty acids of the lipids of testes of rats aged 4 weeks to 6 months were separated and analysed. 2. A decrease in concentration of triglyceride was noted, but there was no significant change in the concentration of phospholipids, plasmalogen or cholesterol during this time. 3. There were no significant differences in the total lipid concentration of palmitic acid, stearic acid, linoleic acid, arachidonic acid and docosatetraenoic acid between the various age groups. 4. A decrease in the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 23 publications
3
62
0
Order By: Relevance
“…The presence of VLC-PUFA in the mammalian testis was fi rst reported in the late 1960s (46)(47)(48)(49)(50). Later, Grogan et al ( 51,52 ) reported that isolated spermatocytes and spermatids synthesized VLC-PUFA from 14 ( 53 ).…”
Section: Distribution Abundance and Biosynthesis Of Vlc-pufamentioning
confidence: 99%
“…The presence of VLC-PUFA in the mammalian testis was fi rst reported in the late 1960s (46)(47)(48)(49)(50). Later, Grogan et al ( 51,52 ) reported that isolated spermatocytes and spermatids synthesized VLC-PUFA from 14 ( 53 ).…”
Section: Distribution Abundance and Biosynthesis Of Vlc-pufamentioning
confidence: 99%
“…Whereas the amount of 22:5n-6 in GPL progressively increases in the testis with spermatogenic cell growth and differentiation ( 13 ), it falls with the involution the mature organ undergoes as it gradually loses its germ cells as a long-term consequence of damaging stem spermatogonia after treatment with a single dose of X-ray irradiation ( 10 ). In the present study, the main GPL classes and subclasses that contribute to these differentiation-related changes were analyzed in pachytene spermatocytes, round spermatids, and residual bodies to contrast them as germ cell products with the VLCPUFA-containing SM and Cer.…”
Section: Seminiferous Tubules and Cell Fractionsmentioning
confidence: 99%
“…According to Davis, Bridges, and Coniglio (1966), the cholesteryl esters and triglycerides decreased with the age of the animal, but Oshima and Carpenter (1968) reported a marked increase of these fractions with age. A significant characteristic of the testicular triglycerides from the adult animal was that they have a high content of unsaturated fatty acids.…”
Section: Calculations Involve D In the Experimentsmentioning
confidence: 99%